Writing or Translating Otherness? (Altre Modernità, 2015)
The paper intends to investigate a new voice in the Italian literary panorama, a voice which makes visible how the notions of nationality, literary canon and mother tongue should be revisioned and rethought.In this age of intensified migration in Europe (and in Italy) transnational women writers are an enriching and challenging factor in many European literatures for the many issues discussed in their novels, among which identity, nationality, ethnicity, gender and language.The essay is divided into two main parts: 1) a theoretical approach aimed at a) outlining the recent debate on World Literature and Transnational literatures, b) rethinking the fruitful discussion within Translation Studies in the last decades, and 2) a textual analysis of a novel, Con il Vento Nei Capelli, written by a Palestinian woman, Salwa Salem.